USING INNOVATIVE TECHNOLOGIES IN MATHEMATICS LESSONS (A CASE STUDY OF THE GEOGEBRA) - Kuchkarova, Arofathon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article shows the advantages of using the GeoGebra program for mathematics teachers in addressing subject-related problems, as well as the issues of the feasibility of integrating this dynamic software into modern education.